Agroecological practices as territorial development: an analytical schema from Brazilian case studies. Issue 4 (7th June 2021) - Levidow, Les; Sansolo, Davis; Schiavinatto, Monica
ABSTRACT: Agroecological practices have been widely promoted as an alternative to the hegemonic agri-food system, yet they also can help to 'green' the system. To strengthen a transformative agroecology, Latin American activists have promoted the concept desenvolvimento territorial rural (DTR or rural territorial development), which has different versions. The dominant version advocates broad multi-actor coalitions to strengthen DTR and thus benefit poor people, yet this obscures rival territorial agendas. An antagonistic version instead analyses how capital accumulation drives societal conflicts, contingently resulting in DTR trajectories. Here an analytical schema helps identify how agroecological practices are appropriated for diverse trajectories of territorial development, illustrated by Brazilian agroforestry case studies.